The crosstalk between COBRA1 and Wnt/Î²-catenin signaling in cervical cancer - Abdelraheem, Omnia Mahmoud (AUC Knowledge Fountain, 2020)
The majority of cancer phenotypes, therapeutic resistance, and clinical prognosis are correlated to dysregulated transcriptional programs within cancer cells. Cofactor of BRCA1 (COBRA1), named also as NELF-B, is one of the principal components of the Negative Elongation Factor (NELF) complex. NELF complex negatively regulates the elongation of transcripts by halting RNA polymerase II at the proximal promoter. It also regulates the transcription of its target genes via interacting with other transcription factors like BRCA1 and AP-1. A previous study by our team showed that the silencing of COBRA1 led to a noted decrease in the steady-state mRNA levels of β-catenin within HeLa cells. This decline indicates an effect for COBRA1 on the Wnt/β-catenin signaling pathway. In our study, quantitative real-time PCR showed that the knockdown of COBRA1 promoted FOXF2 mRNA levels. FOXF2 is a gene known to inhibit HeLa cells proliferation, migration, and invasion in vitro and growth in vivo by regulating the Wnt signaling pathway. Also, our study revealed that the upregulation of FOXF2 in COBRA1 knocked down HeLa cells was accompanied by a suppressed expression of Wnt signaling pathway target genes (β-catenin, C-MYC, and CCND1). The constitutive firing of the Wnt signaling pathway is considered as a second trigger to cervical cancer development after chronic HPV infection. So, COBRA1 silencing and FOXF2 upregulation are accompanied by the downregulation of β-catenin and its downstream target genes. Based on these findings, we speculated that FOXF2 might be the modulator of COBRA1 effects on the β-catenin expression. By performing ChIP assay, the interaction between COBRA1 and the promoter of FOXF2 was proven. Due to the lack of a DNA binding domain in COBRA1, this interaction should be mediated through complex formation. Data obtained from TRANSFAC® Database showed that COBRA1 regulates FOXF2 expression via interacting with ERα, which has a predicted binding site in its promoter. ChIP assay results also indicated that COBRA1 within the NELF complex decreases FOXF2 transcription by pausing the RNAPII at its promoter-proximal region. Altogether, this study could help as a start in identifying and describing the tumorigenic role of COBRA1 mediated by FOXF2 in cervical cancer. Understanding the role of COBRA1 as a transcription factor in cervical cancer opens new insights that have the potential to improve patient care.